Metabolic and Hematological Responses to Endotoxin-Induced Inflammation in Chicks Experiencing Embryonic 2,3,7,8-Tetrachlorodibenzodioxin Exposure - Amaral-Silva, Lara [UNESP]; Tazawa, Hiroshi; Bicego, Kenia Cardoso [UNESP]; Burggren, Warren W. (Wiley-Blackwell, 2020)
Dioxin exposure during bird embryonic development disrupts immunity as well as mechanisms involved in energy metabolism, potentially affecting negatively acute-phase responses to pathogens. Thus, we hypothesized that embryonic exposure to 2,3,7,8-tetrachlorodibenzodioxin (TCDD) changes the metabolism and blood physiology of domestic chicks, affecting their physiological competence for responding to immune challenges. To test this hypothesis, we injected doses of 0, 1.5, and 3 ng TCDD/egg (based on survival experiments) on embryonic day 4 and then measured O(2)consumption and CO(2)production for metabolic rate, ventilation, and body temperature (T-B) in 5-d-old chicks. Then, chicks were injected with lipopolysaccharide (LPS, endotoxin) or saline prior to repeating the physiological measurements. A second chick group exposed to identical TCDD and LPS treatments had blood partial pressure of oxygen, partial pressure of carbon dioxide, pH, bicarbonate concentration, lactate concentration, osmolality, hemoglobin concentration, red blood cell concentration, and hematocrit, as well as T-B, analyzed at 1 and 5 h after LPS injection. Metabolism in chicks embryonically exposed to 1.5 and 3 ng TCDD/egg was up to 37% higher, whereas body mass of chicks exposed to 3 ng TCDD/egg was approximately 6% lower. Chicks embryonically exposed to 3 ng TCDD/egg challenged with LPS showed a relative persistent hypometabolism accompanied by elimination of the normal hematological and osmotic responses to LPS. We conclude that embryonic exposure to TCDD affects posthatching metabolism as well as impairs metabolic, hematological, and osmotic responses to LPS.Environ Toxicol Chem2020;00:1-13. (c) 2020 SETAC
Keywords: Metabolism; Inflammation; Embryos; Avian toxicity; Dioxins; Immunotoxicity